PENGARUHMANAJEMEN LABA, KINERJA KEUANGAN DAN SIZE PERUSAHAAN TERHADAP CORPORATE GOVERNANCE PERCEPTION INDEX DAN IMPLIKASINYA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILTY - RM Riadi; Amries Rusli Tanjung; Edyanus Herman Halim (PEKBIS, 2013)
This research aimed to knew about influence of earning management, financialperformance, and size of company to CGPI and CSR according influence of CGPIwith CSR. The methode of data collection using secondory analysis throughfinancial reporting, cash flow reporting comprehensively including stock value in parvalue and market value. The data was analysing using Microsoft Excell, Lisrel ANFStatistical Program Service Solution (SPSS) version 17. The population countsabout 77 companies, only 48 companies could continued to be analyse causecompelete of data. From analyse of data, the data are normal and get more fit.Comprehensively CGPI, earning management, financial performance and size,could explain CSR about 19%. The rest is explaining by others variabel about 81%(100%-19%). CGP has negative relationship with CSR about 1.52. Earningmanagement has negative relationship with CSR about 3.99. Financial Performance(Tobin Q) has negative relationship with CSR about 0.29. Size have positiverelationship with CSR about 2,28. Comprehensively earning managemen, financialperformance and size could explained CGPI about 15%. The rest has beenexplained by others variabel about 85% (100%-15%). Earning management hasnegative relationship with CGPI about 1.20. Financial Performance has positiverelationship about 0,022 to CGPI and Size has positive relationship about 0.25 toCGPI. Result of this research can conclussion only earning management hasinfluence and significant to CGPI about 23.04%. Financial performance dan size hasinfluence only about 0.64% and 5.29%. To CSR, nor earning management, financialperformance and size has not influence. The influence earning management,financial performance and size are 0.04%, 6.25%, and 7.84%. The influence ofCGPI to CSR only about 9%, it means doesn’t significantly.Keyword: CGPI, CSR and earning management